Ngân hàng bài tập
A

Kết quả của $I=\displaystyle\displaystyle\int x\mathrm{e}^x\mathrm{\,d}x$ là

$I=x\mathrm{e}^x-\mathrm{e}^x+C$
$I=\dfrac{x^2}{2}\mathrm{e}^x+C$
$I=\dfrac{x^2}{2}\mathrm{e}^x+\mathrm{e}^x+C$
$I=x\mathrm{e}^x+\mathrm{e}^x+C$
1 lời giải Sàng Khôn
Trở lại Tương tự
Thêm lời giải
1 lời giải
Sàng Khôn
09:43 23/01/2022

Chọn phương án A.

Đặt $\begin{cases}
u=x\\ v'=\mathrm{e}^x
\end{cases}\Rightarrow\begin{cases}
u'=1\\ v=\mathrm{e}^x.
\end{cases}$

Khi đó $I=x\mathrm{e}^x-\displaystyle\int\mathrm{e}^x\mathrm{\,d}x=x\mathrm{e}^x-\mathrm{e}^x+C$.